A structural model of sales management processes and salesperson behavior performance: The roles of control strategy and supervisor orientation - Alenazi, Sultan Alaswad (Edelweiss Applied Science and Technology, 2026)
This study examines how sales management control strategy and supervisor orientation influence sales organization effectiveness through salesperson behavior performance. Drawing on established sales management and organizational behavior literature, a structural model is developed and empirically tested using survey data collected from 534 salespeople across multiple commercial sectors in Saudi Arabia. Structural equation modeling is employed to assess the relationships among managerial control practices, supervisory orientation, frontline behavioral performance, and organizational effectiveness. The findings indicate that both sales management control strategy and supervisor orientation have significant positive effects on salesperson behavior performance. In turn, salesperson behavior performance is strongly associated with sales organization effectiveness, highlighting the central role of frontline behaviors in translating managerial practices into organizational outcomes. The results underscore the importance of aligning formal control systems with supportive and development-oriented supervisory approaches to enhance sales effectiveness. By adopting a process-oriented perspective, this study contributes to sales management theory and offers practical insights for managers operating in fast-evolving socio-economic and organizational contexts.